Posprandial metabolism in older adults at sea level - Garmendia, Fausto (2003)
OBJETIVE: To determine normal metabolism variations following food ingestion. MATERIAL AND METHODS: A total of 33 normal middle-aged and old adults, 16 female and 17 male, 45-70 years old (average 56,3 ± 7,32), were studied both after a 12-14 hours nocturnal fast and following ingestion of a food mixture containing 730 kcal, 55,4% fat, 37,2% carbohydrates and 7,4% protein, an almost standard breakfast. Blood samples were obtained at fasting state and during 6 hours after the ingestion of the meal described before. Glucose, triglycerides, total cholesterol and HDL cholesterol were measured by enzymatic methods, insuline by radioimmune assay and non–esterified fatty acids (NEFA) by the method of Duncombe. RESULTS: Blood glucose rose from 30 minutes to the 2nd hour; insulin from 30 minutes to the 4th hour, triglycerides rose from the 2nd to 4th hour and then began to decline at the 6th hour without achieving basal value, NEFA diminished from 30 minutes to the 2nd hour and then a rebound was observed even higher than the basal terms at the 6th hour. CONCLUSIONS: The results obtained are considered as a normal pattern for middle–aged and old persons living at sea level and demonstrate that a posprandial study gives a greater information about the metabolism than the carried out only at basal state.